THE SITUATION OF RETURNED MIGRANT WORKERS IN REPUBLIC OF MOLDOVA - VACULOVSCHI DORIN; DOGARU RAISA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
In recent years, the public authorities of the Republic of Moldova are drawing increasing attention to the phenomenon of return migration, seeing in it an important reserve for increasing human potential, which is extremely necessary for the prospects for sustainable development of country. In this context, the issue of integration of migrant workers returning to the labor market in the Republic of Moldova is becoming one of the priority objectives of current employment policies in the Republic of Moldova. This article aims to analyze the situation of returned migrants based on the results of the latest studies (ILO 2020, ODIMM, ANOFM, etc.) related to the integration of returned migrants on the labor market in the Republic of Moldova, access to employment services provided by ANOFM to returned migrants and the financing of the business of returned migrants and their families. The impact of the COVID-19 pandemic on the situation of labor migration from the Republic of Moldova, especially on return migration is also analyzed